Calitatea vieții în România - Bălașa, Ana; Mărginean, Ioan; Sandu, Ilie; Socol, Gheorghe (Calitatea Vieții, 1992)
This a synthesis of the main results of the third consecutive annual research: concerning the diagnosis of the quality of life in Romania, published in extenso in a ’Volume at the Center of Information, and Economic Documentation (series, Quality of Life", no. 14/1992 ). The research was accomplished in May 1992 using a representative national sample of 1,516 individuals from 28 towns and 33 villages.